2023
DOI: 10.1039/d3dt00678f
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and dielectric constants of topologically defected boron nitride nanotubes

Abstract: Boron nitride nanotubes (BNNTs) form a promising low-dimensional piezoelectric material that may be used for multifunctional energy-harvesting nanopiezoelectronic devices. The piezoelectric and dielectric constants of a single-walled BNNT are determined...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…In the absence of a centre of symmetry, the broken inversion symmetry of h-BN monolayers allows for piezoelectric properties, this has led to recent studies on h-BN for this application. [35][36][37][38][39] Although r-BN shares this structural property and potential for piezoelectricity in addition to the abovementioned properties, the literature on properties and applications of r-BN is relatively limited.…”
Section: Properties and Applications Of Sp 2 -Boron Nitridementioning
confidence: 99%
“…In the absence of a centre of symmetry, the broken inversion symmetry of h-BN monolayers allows for piezoelectric properties, this has led to recent studies on h-BN for this application. [35][36][37][38][39] Although r-BN shares this structural property and potential for piezoelectricity in addition to the abovementioned properties, the literature on properties and applications of r-BN is relatively limited.…”
Section: Properties and Applications Of Sp 2 -Boron Nitridementioning
confidence: 99%
“…Similar conclusions that were previously reported suggested that BNNTs can form a more effective interface with hydrocarbon-based engineering polymers. [21][22][23][24][25][26] The introduction of vacancies and oxidation defects in BNNT served to improve the transverse damping characteristics of the nanocomposites, whereas their elasticity deteriorated. A comparison of the loss tangent of BNNT-reinforced composites at different frequencies revealed no clear difference in the extent to which B and N vacancies tailored the damping properties of nanocomposites.…”
mentioning
confidence: 99%
“…25 Although the hybridisation of C–C bonds in CNTs using intrinsic or designed defects improves their elasticity, only few studies have been devoted to defect engineering in BNNTs. 26 These studies included investigations of the impact of structural defects in BNNTs, such as vacancy and oxidation defects generated during their thermochemical synthesis, on the load transfer and energy dissipation at the interface with engineering materials. In this study, based on vacancy and oxidation defects, we performed comparative molecular dynamics (MD) simulations to analyse the viscoelastic damping properties of BNNT- and CNT-reinforced polyether ether ketone (PEEK) nanocomposites.…”
mentioning
confidence: 99%
See 1 more Smart Citation